2011
DOI: 10.1007/s11854-011-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint Schur algorithm and orthogonal rational functions, I: Convergence properties

Abstract: Classical Schur analysis is intimately related to the theory of orthogonal polynomials on the circle. We investigate the connection between multipoint Schur analysis and orthogonal rational functions. Specifically, we study the convergence of the Wall rational functions via the development of a rational analogue to the Szegő theory in the case that interpolation points may accumulate on the unit circle. This leads to a generalization of results in [22,10], and new types of asymptotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
(86 reference statements)
0
17
0
Order By: Relevance
“…First, note that (8.6) is sufficient for the Nevanlinna-Pick problem in R 0 to be determinate but not necessary (see [27,Chapter IV,Example 4.2]). It should also be noted that, under the Szegö condition and the negation of the Blashcke type condition, the locally uniform convergence of multipoint diagonal Padé approximants for ϕ ∈ R[α, β] was proved in [46] (see also [6]). Now, we are also able to adapt Theorem 5.5 for the self-adjoint case.…”
Section: Convergence Of Multipoint Padé Approximantsmentioning
confidence: 99%
“…First, note that (8.6) is sufficient for the Nevanlinna-Pick problem in R 0 to be determinate but not necessary (see [27,Chapter IV,Example 4.2]). It should also be noted that, under the Szegö condition and the negation of the Blashcke type condition, the locally uniform convergence of multipoint diagonal Padé approximants for ϕ ∈ R[α, β] was proved in [46] (see also [6]). Now, we are also able to adapt Theorem 5.5 for the self-adjoint case.…”
Section: Convergence Of Multipoint Padé Approximantsmentioning
confidence: 99%
“…In a recent paper [3], we proved the following asymptotics of rational Christoffel functions. 1]. Assume that for some η > 0, the poles {α j } satisfy for all j ≥ 1,…”
Section: Introductionmentioning
confidence: 99%
“…Note the key restriction that the poles stay away from [−1, 1]. In some results on asymptotics of orthogonal rational functions [1], such a restriction has been replaced by a Blaschke type assumption that…”
Section: Introductionmentioning
confidence: 99%
“…There has been much interest in the theory of orthogonal rational functions (ORFs) on the unit circle, partly due to their connection to the multipoint Schur algorithm [1,9,21] and partly due to the fact that they are natural generalizations of orthogonal polynomials to the case where not all the poles are at infinity. ORFs on the complex unit circle were first introduced by Džrbašian in the 1960s [15], and have been studied extensively during the past few decades; e.g.…”
Section: Introductionmentioning
confidence: 99%
“…. , (1) which was a generalization of the system solved by Szegő orthogonal polynomials [19]. He showed that if the coefficients in the above system were l 1 summable then certain solutions to the above equations formed a system of polynomials bi-orthogonal with respect to a complex measure which is absolutely continuous with respect to Lebesgue measure.…”
Section: Introductionmentioning
confidence: 99%